The Pamir Frontal Thrust Fault: Holocene Full‐Segment Ruptures and Implications for Complex Segment Interactions in a Continental Collision Zone. Issue 12 (14th December 2021) - Patyniak, M.; Landgraf, A.; Dzhumabaeva, A.; Baikulov, S.; Williams, A. M.; Weiss, J.R.; Hilley, G. E.; Preusser, F.; Abdrakhmatov, K. E.; Arrowsmith, R. J; Strecker, M. R.
Abstract: The Pamir Frontal Thrust (PFT) of the Trans‐Alai Range in Central Asia is the principal active fault of the intracontinental convergence zone between the Pamir and Tien Shan. Its northward propagation is reflected by frequent seismic activity and ongoing crustal shortening. Recent and historic earthquakes exhibit complex rupture patterns within and across seismotectonic segments bounding the Trans Alai, challenging our understanding of fault interaction and seismogenic potential. We provide paleoseismic data from five trenches along the central PFT segment (cPFT) and interpret five and possibly six paleoearthquakes that have ruptured since ∼7 ka and 16 ka, respectively. Our results indicate that at least three major earthquakes ruptured the full‐segment length and possibly crossed segment boundaries with a recurrence interval of ∼1.9 kyr and potential magnitudes of up to M w 7.4. We did not find evidence for great (i.e., M w ≥8) earthquakes. However, discrepancies between slip and rupture extent during apparent partial segment ruptures in the western half of the cPFT, combined with significantly higher scarp offsets, indicate a more mature fault section with potential for future fault linkage. We estimate an average rate of horizontal motion for the cPFT of 4.1 ± 1.5 mm/yr during the past ∼5 kyr, which does not fully match the GNSS‐derived present‐day shortening rate of ∼10 mm/yr. This suggests a complex distribution of strain accumulation and potential slip partitioning between the cPFT and additional faults and folds within the Pamir that may be associated with a partially locked regional décollement. Plain Language Summary: The northward movement of the Trans‐Alai mountain front at the northwestern edge of the India‐Eurasia collision zone is associated with significant seismic activity across the northern rim of the Pamir Mountains in Central Asia. Historical earthquakes and faulting in this location are complex and not well understood. Here, we present the results from paleoseismologic excavations including evidence for five or possibly six major earthquakes that have occurred in the past 16, 000 years. These events have a recurrence of ∼1, 900 years and potential magnitudes of up to M w 7.4. We estimate that the central part of the major Pamir Frontal Thrust fault zone has moved at a rate of 4.1 ± 1.5 mm/yr during the past ∼5, 000 years, which is different from the present‐day shortening rate estimates based on geodetic data. The discrepancy points towards a more complex pattern of faulting and a broader distribution of active deformation than previously suggested. Key Points: New paleoseismological data along the Pamir Frontal Thrust (Kyrgyzstan) reveal five events since ∼7 ka and possibly six since ∼16 ka At least three earthquakes with a potential magnitude of M w 7.4 ruptured the full‐segment length, and possibly crossed segment boundaries The central Pamir Frontal Thrust has accommodated 4.7 ± 1.7 mm/yr of dip‐slip deformation during the Holocene